2021
DOI: 10.1002/jocb.525
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Perceived Benefits of Nature for Creativity

Abstract: Experience of nature is widely linked to well‐being, including psychological restoration. Benefits to creativity have been explored in a limited number of studies which refer to theories of restorative environments as frameworks, but it is unclear which aspects of the environment and person–nature transactions are implicated in these processes. In this study, N = 20 members of the British public were interviewed regarding the relevance of natural environments for their personal and professional creative activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Another issue is the cost. Because it can be costly to set up VR labs with top-tier hardware and software licenses, it is a less practical tool for colleges with low funding (Ratcliffe, Gatersleben, Sowden, & Korpela, 2022). Additionally, although VR provides an immersive experience, prolonged use can cause physical discomfort, with users reporting symptoms including drowsiness, nausea, and eye strain, which are known as VR sickness.…”
Section: Benefits and Challenges Of Vr In Architectural Educationmentioning
confidence: 99%
“…Another issue is the cost. Because it can be costly to set up VR labs with top-tier hardware and software licenses, it is a less practical tool for colleges with low funding (Ratcliffe, Gatersleben, Sowden, & Korpela, 2022). Additionally, although VR provides an immersive experience, prolonged use can cause physical discomfort, with users reporting symptoms including drowsiness, nausea, and eye strain, which are known as VR sickness.…”
Section: Benefits and Challenges Of Vr In Architectural Educationmentioning
confidence: 99%
“…It also encourages physical activity, increases fitness, and supports a healthy lifestyle ( Brymer et al, 2010 ; Lawton et al, 2017 ). Studies have shown that time spent in nature positively affects mental and emotional health, reduces stress, improves mood, and encourages creativity ( Tinsley and Eldredge, 1995 ; Iwasaki et al, 2005 ; Li et al, 2021 ; Onu et al, 2022 ; Ratcliffe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%